Electrochemical enrichment method of nitrite and application
By using Cu-based PVDF film as cathode material, selective reduction of nitrate to nitrite is achieved, the problem of low nitrate reduction efficiency in the Anammox reaction is solved, and the nitrogen removal efficiency and stability of the cathode material are improved.
Patent Information
- Application Number
- CN202510016172.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-12-31
- Filing Date
- 2025-01-06
- Publication Date
- 2025-03-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, the reduction efficiency of the Anammox reaction associated with nitrate is low, and the cathode material is susceptible to contamination and corrosion, which limits the wide application of NO3− electrochemical reduction technology.
The Cu-based PVDF film is used as the cathode material, and the nitrate is selectively reduced to nitrite through electrocatalytic reaction to achieve nitrite enrichment. This method improves the stability of the Cu-based metal mesh through the protection of PVDF film and avoids pollution and corrosion.
Under low current density conditions, efficient reduction of nitrate to nitrite is achieved, which improves the denitrification efficiency of Anammox, extends the service life of the cathode material, and reduces process costs.
Smart Images

Figure CN119638022A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sewage denitrification, in particular to an electrochemical enrichment method of nitrite and its application. Background Art
[0002] In the field of wastewater denitrification, the anaerobic ammonia oxidation (Anammox) process does not require an organic carbon source compared to traditional nitrification and denitrification technology, reduces sludge production by 90% and does not produce greenhouse gases. It has significant low-carbon characteristics and leads a new direction for sustainable development of wastewater treatment. However, there are still many technical bottlenecks in Anammox, which limits its large-scale application in mainstream wastewater treatment. For example, the Anammox reaction will produce about 11% nitrate (NO3 − ) makes its maximum total nitrogen removal rate unable to exceed 90%; NO3 − The accumulation of nitrite (NO2 − The instability of the supply of ) has increased Anammox's reliance on traditional denitrification and short-cut nitrification processes. The short-cut denitrification process proposed in recent years can convert NO3 − Converted to NO2 − , is an ideal biotechnology that can be coupled with Anammox, but this process and traditional nitrification and denitrification technology face problems such as demand for organic carbon sources, excessive sludge production, susceptibility to environmental conditions, and greenhouse gas emissions. In contrast, electrochemical reduction technology has high treatment efficiency, low equipment cost, easy operation, low sludge production, and is environmentally friendly. − It shows great application potential.
[0003] NO3 − Electrochemical reduction technology is one of the most promising ways to balance the global nitrogen cycle. − Reducing NO3 to harmless nitrogen gas can solve the nitrogen pollution in water environment. − Reduced to ammonia, thus achieving the goal of "turning waste into treasure". Therefore, nitrogen and ammonia are usually considered to be NO3 − The main target product of electrochemical reduction. As NO3 − The main intermediate product in the reduction process, NO2 − Often viewed as a toxic byproduct, NO2 − It is also the electron acceptor in the Anammox reaction and plays an important role in the Anammox process. −The electrochemical reduction to nitrogen and ammonia involves complex 5-electron side reactions and 8-electron complete reduction processes, respectively, both of which have the problems of low Faradaic efficiency and slow reaction kinetics. − The formation of the whole NO3 − The initial and rate-limiting step of the reduction mechanism, how to selectively convert the NO3 associated with Anammox − Reduction to NO2 − It is an ideal means to improve the denitrification efficiency of Anammox, but the related technology has not been reported at home and abroad.
[0004] Copper (Cu) is a catalyst for NO3 − One of the most active metals in reduction reactions, with highly occupied d orbitals, capable of efficiently absorbing NO3 − , and has a significant inhibitory effect on the hydrogen evolution reaction. Cu-based metals are therefore widely used in the preparation of NO3 − The cathode material of the reduction system. However, during use, this type of cathode material is easily contaminated and corroded after contacting the complex components in the electrolyte, resulting in a decrease in reduction efficiency. Therefore, the lack of protection of the cathode material during use is also a limitation of NO3 − This is an important factor for the widespread application of electrochemical reduction technology. Summary of the invention
[0005] In view of the above-mentioned problems existing in the prior art, the present invention provides a method and application of electrochemical enrichment of nitrite. The Cu-based PVDF membrane prepared by the method of the present application can alleviate the pollution and corrosion of the surface of the Cu-based metal mesh and improve the stability of the cathode material. The electrocatalytic reduction system in the present application can realize the selective reduction of nitrate to nitrite.
[0006] To achieve the above object, the technical solution provided by the present invention is as follows:
[0007] In a first aspect, the present application provides a method for electrochemical enrichment of nitrite, wherein the method comprises selectively reducing nitrate to nitrite by an electrocatalytic reaction, thereby achieving nitrite enrichment, wherein the reduction reaction occurs on the surface of a Cu-based PVDF membrane.
[0008] Optionally, the following steps are included:
[0009] 1) The Cu-based PVDF membrane is used as the cathode and connected to the negative electrode of the DC power supply, and the two anode materials are connected to the positive electrode of the power supply. The cathode and the two anodes are parallel and opposite to each other and maintain a certain distance to construct an electrocatalytic reduction system;
[0010] 2) The electrocatalytic reduction system is immersed in a nitrate solution, and the nitrate is selectively reduced to nitrite under conditions of constant current density and continuous stirring to achieve nitrite enrichment.
[0011] Optionally, the distance between the cathode and the anode is 0.5-1.5 cm.
[0012] Optionally, the constant current density is 0.1-0.3 mA / cm 2 .
[0013] Optionally, the anode material is the same area as the cathode material.
[0014] Optionally, the anode material includes one or more of carbon, titanium, platinum, lead, nickel, iridium, ruthenium, stainless steel and boron-doped diamond, and the anode material is in the form of sheet, plate, mesh, cloth or foam.
[0015] Optionally, the preparation of the Cu-based PVDF membrane comprises the following steps:
[0016] 1) mixing raw materials including polyvinylidene fluoride, a porogen and an organic solvent to obtain a film casting solution, and coating the film casting solution onto a Cu-based metal mesh;
[0017] 2) placing the Cu-based metal mesh coated with the plating solution in a coagulation bath to coagulate into a film, and after the film falls off, washing the film in deionized water, and drying to obtain the Cu-based PVDF film.
[0018] Optionally, the raw materials for preparing the Cu-based PVDF membrane include the following components in parts by weight: 79-83 parts of organic solvent, 9-15 parts of polyvinylidene fluoride, and 6-8 parts of porogen.
[0019] Optionally, the Cu-based metal mesh has a thickness of 100-200 μm and a pore size of 100-300 μm, and the material of the Cu-based metal mesh is one of pure copper, copper oxide, and an alloy of copper or copper oxide and other metals or non-metals.
[0020] Optionally, the organic solvent is N, N-dimethylacetamide.
[0021] Optionally, the porogen is polyvinyl pyrrolidone, polyethylene glycol, hexadecyltrimethylammonium bromide or sodium dodecyl sulfate.
[0022] Optionally, the raw material mixing condition is stirring at 80-90° C. for 12-16 h.
[0023] Optionally, the casting solution is degassed and then coated onto a Cu-based metal mesh, and the coating film layer has a thickness of 250-400 μm.
[0024] The coating film thickness is controlled to ensure the wrapping of the Cu-based metal mesh by the film layer.
[0025] Optionally, in step 2), the membrane is immersed in deionized water for 48-72 hours to remove the organic solvent; and the drying condition is 30-40° C. for 24-48 hours.
[0026] Optionally, the Cu-based metal mesh coated with the casting solution is first placed in air for 5-10 s before being placed in a coagulation bath.
[0027] In a second aspect, the present application provides an application of the electrochemical enrichment method of nitrite described in the first aspect in denitrification by anaerobic ammonia oxidation process.
[0028] The invention first prepares a casting solution, and then coats the casting solution on the surface of a Cu-based metal mesh to prepare a Cu-based PVDF membrane; the Cu-based PVDF membrane is used as a cathode material and connected to the negative electrode of a DC power supply, two anode materials with the same area as the cathode are connected to the positive electrode of the power supply, and the positive and negative electrodes are parallel and opposite to each other and maintain a distance of 0.5-1.5 cm to construct an electrocatalytic reduction system; the electrocatalytic reduction system is immersed in a nitrate solution at a temperature of 0.1-0.3 mA / cm 2 Under the conditions of constant current density and continuous stirring, nitrate can be selectively reduced to nitrite to achieve nitrite enrichment. In the present invention, the PVDF layer on the surface of the Cu-based PVDF membrane fully wraps the Cu-based metal mesh, plays a good protective role, and prevents the substances in the sewage from directly contacting the Cu-based metal mesh to cause corrosion or pollution on its surface, thereby improving the use stability and sustainable utilization of the Cu-based PVDF membrane; the PVDF layer has a large pore size and high porosity, which will not hinder the contact reaction between the Cu-based metal mesh and the nitrate in the water, ensuring the high efficiency of the electrocatalytic reduction process. The electrocatalytic reduction system constructed with the Cu-based PVDF membrane as the cathode can efficiently reduce nitrate to nitrite under low current density conditions, with a fast catalytic reaction speed and low power consumption, which is conducive to the continuous accumulation of nitrite; the electrocatalytic reduction system is simple to operate, the electrode area is controllable, and the space occupied is small. It can be conveniently loaded in various reactors of the anaerobic ammonia oxidation process, and the denitrification efficiency of anaerobic ammonia oxidation can be significantly improved during long-term operation, and will not have an adverse effect on the operation of the reactor. The electrochemical enrichment method of nitrite provided by the present invention is the first attempt to reduce nitrate with the goal of enriching nitrite. Its application in improving the denitrification efficiency of the anaerobic ammonium oxidation process is also the first combination of nitrate electrochemical reduction technology and the anaerobic ammonium oxidation process. This method provides a new idea for the supply of nitrite in the anaerobic ammonium oxidation process, which will help promote the sustainable development of this process in the field of sewage treatment.
[0029] Compared with the prior art, the present invention has the following characteristics:
[0030] 1) The electrochemical enrichment method of nitrite provided by the present invention can reduce nitrate to nitrite under low current density conditions, has high selectivity, Faraday efficiency and yield, can significantly reduce the generation of ammonium salts and achieve rapid enrichment of nitrite, thereby achieving the removal of nitrate associated with the anaerobic ammonium oxidation process and continuously providing nitrite substrate, thereby improving the denitrification efficiency of anaerobic ammonium oxidation.
[0031] 2) The Cu-based PVDF membrane provided by the present invention has good nitrate reduction efficiency. The PVDF membrane with large pore size and high porosity on its surface can provide sufficient protection for the internal Cu-based metal mesh, reduce the corrosion or contamination of the metal mesh after contact with substances in sewage, and ensure the stability and sustainable utilization of the electrocatalytic cathode material.
[0032] 3) The electrocatalytic reduction system constructed by the present invention can use various Cu-based metal meshes to make Cu-based PVDF membranes, and can be matched with anode materials of various materials. The selection range of electrode materials is wide, the system operation is highly flexible, the anode and cathode areas can be adjusted at will and the spacing is small, and the footprint is small, which is conducive to large-scale production and engineering applications.
[0033] 4) The nitrite enrichment method provided by the present invention is simple and easy, has low requirements for equipment, requires a small current density, has low power consumption and process costs, does not produce secondary pollution, has low requirements for sewage temperature, pH, and components, can be easily loaded into various anaerobic ammonium oxidation reactors, and has important application value in sewage treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 is the surface of the Cu-based PVDF membrane prepared in Example 1 ( Figure 1 a) and cross section ( Figure 1 b) Membrane pore morphology and cross-sectional Cu-based metal mesh morphology ( Figure 1 c) Scanning electron microscope image and elemental composition spectrum of Cu-based PVDF membrane surface energy spectrum analysis ( Figure 1 d).
[0035] Figure 2 The cyclic voltammetry (CV) of the Cu-based PVDF membrane prepared in Example 1 in an electrolyte with or without nitrate added is shown in FIG. Figure 2 a) Linear sweep voltammetry (LSV, Figure 2 b) and electrochemical impedance spectroscopy (EIS, Figure 2 c) Characterization results.
[0036] Figure 3 Schematic diagram of the structure of the electrocatalytic reduction system in the embodiment.
[0037] Figure 4In the electrocatalytic reduction system constructed in Example 1, Na2SO4 solution ( Figure 4 a) and deionized water ( Figure 4 b) After 0.2 mA / cm 2 The current density of nitrate nitrogen (NO3 − -N) and the removal efficiency (RE) of nitrite nitrogen (NO2 − -N) and ammonia nitrogen (NH4 + -N) selectivity (s); after adding Na2SO4 solution and deionized water into the electrocatalytic reduction system, the 2 Reduction of NO3 at current density − -N is NO2 − -N and NH4 + -N Faraday efficiency ( Figure 4 c) and yield ( Figure 4 d) Changes with reaction time.
[0038] Figure 5 The electrocatalytic reduction system constructed in Example 1 with a Cu-based PVDF membrane as the cathode was loaded into an anaerobic ammonium oxidation membrane bioreactor and operated for 190 days. The nitrogen element (NH4 + 、NO2 − and NO3 − ) concentration change ( Figure 5 a) and changes in total nitrogen volumetric load (TNLR), total nitrogen removal load (TNRR) and total nitrogen removal efficiency (TNRE) ( Figure 5 b);
[0039] Description of reference numerals:
[0040] 1. Anode; 2. Cathode; 3. Stirrer; 4. DC power supply. DETAILED DESCRIPTION
[0041] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0042] The experimental methods used in the embodiments of the present invention are conventional methods unless otherwise specified.
[0043] Unless otherwise specified, the reagents and materials used in this example can be purchased conventionally.
[0044] The invention provides an electrochemical enrichment method and application of nitrite. In order to achieve efficient enrichment of nitrite, the invention first prepares a uniform casting solution, and then coats the casting solution on the surface of a Cu-based metal mesh to prepare a Cu-based PVDF membrane; the Cu-based PVDF membrane is used as a cathode and connected to the negative electrode of a DC power supply, two anode materials with the same area as the cathode are connected to the positive electrode of the power supply, and the positive and negative electrodes are parallel and opposite to each other and maintain a distance of 0.5-1.5 cm to construct an electrocatalytic reduction system; the electrocatalytic reduction system is immersed in a nitrate solution at 0.1-0.3 mA / cm 2 Under the conditions of constant current density and continuous stirring, nitrate is selectively reduced to nitrite to achieve nitrite enrichment. The electrochemical enrichment method of nitrite provided by the present invention is different from the traditional nitrate reduction technology for producing ammonia or nitrogen. The method innovatively reduces nitrate to nitrite, and the application scenario is anaerobic ammonia oxidation denitrification. The nitrate associated with anaerobic ammonia oxidation can be reduced to nitrite and recycled as a substrate, thereby significantly improving the denitrification efficiency of anaerobic ammonia oxidation; the equipment process of this method is simple, the operation is convenient, the selection range of anode and cathode materials is wide, the electrode area can be adjusted at will, the electrode spacing is narrow, the footprint is small, and it can be flexibly installed in various anaerobic ammonia oxidation reactors; the method has high nitrate reduction efficiency and nitrite selectivity, can achieve rapid enrichment of nitrite, has low requirements on water environment conditions, and requires low current density and power consumption, showing broad application prospects in coupling and optimizing anaerobic ammonia oxidation processes.
[0045] Embodiment 1:
[0046] (1) Preparation of Cu-based PVDF membrane
[0047] After PVDF and polyvinyl pyrrolidone porogen were dried at 85°C for 36 h, 12 g PVDF and 7 g polyvinyl pyrrolidone porogen were weighed and added to 81 g N, N-dimethylacetamide, and stirred at 85°C for 14 h to prepare a uniform casting solution; after the casting solution was allowed to stand for degassing for 30 h, it was evenly coated on a pure copper mesh with a thickness of 100 μm and a pore size of 200 μm fixed on a dry glass plate using a film scraper, and the coating film thickness was 300 μm; the pure copper mesh coated with the casting solution was allowed to stand in the air for 8 s and then placed in a deionized water coagulation bath, and after it fell off naturally, it was immersed in deionized water for 60 h, and dried in an oven at 35°C for 36 h to obtain a Cu-based PVDF membrane.
[0048] (2) Electrochemical enrichment of nitrite
[0049] 10 × 10 cm 2The Cu-based PVDF membrane is connected to the negative electrode of the DC power supply as the cathode 2, and two Ti mesh anodes 1 with the same area as the cathode are connected to the positive electrode of the DC power supply 4. The cathode 2 is arranged between the two anodes 1, and the cathode and the anode are parallel to each other and maintained at a distance of 1 cm to obtain an electrocatalytic reduction system; the electrocatalytic reduction system is immersed in a nitrate solution at 0.2 mA / cm 2 Under the conditions of a constant current density of and continuous stirring by the stirrer 3, nitrate is selectively reduced to nitrite to achieve nitrite enrichment.
[0050] Figure 1 is the surface of the Cu-based PVDF membrane prepared in this example ( Figure 1 a) and cross section ( Figure 1 b) Membrane pore morphology and cross-sectional Cu-based metal mesh morphology ( Figure 1 c) Scanning electron microscope image and elemental composition spectrum of Cu-based PVDF membrane surface energy spectrum analysis ( Figure 1 d). From Figure 1 It can be seen that the PVDF membrane surface on the Cu-based PVDF membrane has larger membrane pores along the Cu lines in the Cu mesh ( Figure 1 a), the porosity of the membrane is high and uniform ( Figure 1 b), the Cu mesh is sandwiched between the PVDF membrane and has good wrapping properties ( Figure 1 c), no obvious Cu element was detected on the film surface ( Figure 1 d), indicating that the PVDF membrane has good protection for the Cu mesh and will not hinder the contact reaction between the Cu mesh and nitrate in water, which can improve the stability and sustainable utilization of the Cu-based PVDF membrane.
[0051] Figure 2 The cyclic voltammetry (CV) of the Cu-based PVDF membrane prepared in this example in an electrolyte with or without nitrate added is shown in FIG. Figure 2 a) Linear sweep voltammetry (LSV, Figure 2 b) and electrochemical impedance spectroscopy (EIS, Figure 2 c) Characterization results. Figure 2 It can be seen that compared with the case where no nitrate is added to the electrolyte, the CV curve of the Cu-based PVDF membrane after adding nitrate has a significantly stronger reduction peak, the LSV curve has a stronger current density response and a higher positive onset potential, and the EIS curve has a smaller arc radius, indicating that the Cu-based PVDF membrane has significant nitrate reduction activity and lower charge transfer resistance, proving that it has good application potential in the selective reduction of nitrate and nitrite enrichment.
[0052] Figure 3This is a schematic diagram of the installation of the electrocatalytic reduction system constructed in this embodiment. It can be seen from the figure that the electrocatalytic reduction system is constructed with a Cu-based PVDF membrane as the cathode and two anodes in parallel and opposite to each other, and realizes the reduction of nitrate and electrochemical enrichment of nitrite under the conditions of continuous current and stirring.
[0053] Figure 4 In the electrocatalytic reduction system constructed in this embodiment, Na2SO4 solution ( Figure 4 a) and deionized water ( Figure 4 b) After 0.2 mA / cm 2 The current density of nitrate nitrogen (NO3 − -N) and the removal efficiency (RE) of nitrite nitrogen (NO2 − -N) and ammonia nitrogen (NH4 + -N) selectivity (s); after adding Na2SO4 solution and deionized water into the electrocatalytic reduction system, the 2 Reduction of NO3 at current density − -N is NO2 − -N and NH4 + -N Faraday efficiency ( Figure 4 c) and yield ( Figure 4 d) Changes with reaction time. Figure 4 Display, at 0.2 mA / cm 2 At a constant current density of 1.34°, as the electrocatalytic time was extended from 2 h to 10 h, the nitrate removal efficiency of the constructed electrocatalytic reduction system with the addition of Na2SO4 electrolyte increased from 0.7% to 17.4%, the nitrite selectivity increased from 54.0% to 81.5%, and the ammonium selectivity continued to decrease from 31.3% to 7.5% ( Figure 4 a); The Faraday efficiency of nitrite production increased from 3.6% to 27.2%, and the nitrite yield increased from 1.4 mmol / h / m 2 Increased to 10.2 mmol / h / m 2 , while the Faradaic efficiency and yield of ammonium salt production remained almost unchanged ( Figure 4 c and 4d); the changes in nitrate removal efficiency, product selectivity, Faraday efficiency and yield of the constructed electrocatalytic reduction system when deionized water was added were similar to those of Na2SO4 electrolyte ( Figure 4 The above results show that the electrochemical enrichment method of nitrite provided by the present invention has good nitrate reduction efficiency in both Na2SO4 electrolyte and deionized water. 2At a low current density, nitrate can be selectively reduced to nitrite and the production of ammonium salt can be inhibited. The reduction efficiency gradually increases with the reaction time, which is conducive to the continuous accumulation of nitrite in the system.
[0054] Figure 5 The electrocatalytic reduction system with Cu-based PVDF membrane as cathode in this embodiment was loaded into the anaerobic ammonium oxidation membrane bioreactor and operated for 190 days. The nitrogen element (NH4 + 、NO2 − and NO3 − ) concentration change ( Figure 5 a) and changes in total nitrogen volumetric load (TNLR), total nitrogen removal load (TNRR) and total nitrogen removal efficiency (TNRE) ( Figure 5 b). Figure 5 Showing that MBR equipped with electrocatalytic reduction system 还原 After the electrocatalytic reaction started, the concentrations of nitrate and ammonium in the effluent were similar to those in the control MBR (MBR 对照 —without electrocatalytic reduction system) is significantly lower than that of MBR 还原 TNRR (0.97–1.04 kg N / m 3 / d) is significantly higher than MBR 对照 (0.91–0.97 kg N / m 3 / d), MBR 还原 The average TNRE (92.25 ± 0.55%) was significantly higher than that of MBR. 对照 (86.42 ± 0.82%). It can be seen that the electrochemical enrichment method of nitrite provided by the present invention can efficiently reduce the nitrate associated with anaerobic ammonium oxidation to nitrite during the long-term operation of the anaerobic ammonium oxidation process, so that the nitrite can participate in the anaerobic ammonium oxidation reaction again and further consume ammonium salt, which has a significant effect on improving the denitrification efficiency of the anaerobic ammonium oxidation process.
[0055] Embodiment 2:
[0056] (1) Preparation of Cu-based PVDF membrane
[0057] After PVDF and polyethylene glycol porogen were dried at 80°C for 24 h, 9 g PVDF and 8 g polyethylene glycol porogen were weighed and added to 83 g N, N-dimethylacetamide, and stirred at 80°C for 12 h to prepare a uniform casting solution; after the casting solution was allowed to stand for degassing for 24 h, it was evenly coated on a CuO mesh with a thickness of 120 μm and a pore size of 100 μm fixed on a dry glass plate using a scraper, and the coated film thickness was 250 μm; the CuO mesh coated with the casting solution was allowed to stand in the air for 5 s and then placed in a deionized water coagulation bath, and after it fell off naturally, it was immersed in deionized water for 48 h, and dried in an oven at 30°C for 24 h to obtain a Cu-based PVDF membrane.
[0058] (2) Electrochemical enrichment of nitrite
[0059] 8 × 8 cm 2 The Cu-based PVDF membrane is connected to the negative electrode of the DC power supply as the cathode, and two Ti / IrO2 anode materials with the same area as the cathode are connected to the positive electrode of the power supply. The positive and negative electrodes are parallel and face each other with a distance of 0.5 cm to construct an electrocatalytic reduction system. The electrocatalytic reduction system is immersed in a nitrate solution at 0.3 mA / cm 2 Under the conditions of constant current density and continuous stirring, nitrate is selectively reduced to nitrite to achieve nitrite enrichment.
[0060] Embodiment 3:
[0061] (1) Preparation of Cu-based PVDF membrane
[0062] After PVDF and hexadecyltrimethylammonium bromide porogen were dried at 90°C for 48 h, 15 g PVDF and 6 g hexadecyltrimethylammonium bromide porogen were weighed and added to 79 g N, N-dimethylacetamide, and stirred at 90°C for 16 h to prepare a uniform casting solution; after the casting solution was allowed to stand for degassing for 36 h, it was evenly coated on a Cu / Fe alloy mesh with a thickness of 200 μm and a pore size of 300 μm fixed on a dry glass plate using a scraper, and the thickness of the coating layer was 400 μm; the Cu / Fe alloy mesh coated with the casting solution was allowed to stand in the air for 10 s and then placed in a deionized water coagulation bath, and after it fell off naturally, it was immersed in deionized water for 72 h, and dried in an oven at 40°C for 48 h to obtain a Cu-based PVDF membrane.
[0063] (2) Electrochemical enrichment of nitrite
[0064] 15 x 15 cm 2The Cu-based PVDF membrane was connected to the negative electrode of a DC power supply as a cathode, and two Pt anode materials with the same area as the cathode were connected to the positive electrode of the power supply. The positive and negative electrodes were parallel and opposite to each other and kept 1.5 cm apart to construct an electrocatalytic reduction system. The electrocatalytic reduction system was immersed in a nitrate solution at 0.2 mA / cm 2 Under the conditions of constant current density and continuous stirring, nitrate is selectively reduced to nitrite to achieve nitrite enrichment.
[0065] Embodiment 4:
[0066] (1) Preparation of Cu-based PVDF membrane
[0067] After PVDF and sodium dodecyl sulfate porogen were dried at 83°C for 30 h, 11 g PVDF and 6.5 g sodium dodecyl sulfate porogen were weighed and added into 82.5 g N, N-dimethylacetamide, and stirred at 82°C for 13 h to prepare a uniform casting solution; after the casting solution was allowed to stand for degassing for 27 h, it was evenly coated on a Cu / Pd alloy mesh with a thickness of 150 μm and a pore size of 150 μm fixed on a dry glass plate using a scraper, and the thickness of the coated film layer was 340 μm; the Cu / Pd alloy mesh coated with the casting solution was allowed to stand in the air for 7 s and then placed in a deionized water coagulation bath, and after it fell off naturally, it was immersed in deionized water for 50 h, and dried in an oven at 32°C for 30 h to obtain a Cu-based PVDF membrane.
[0068] (2) Electrochemical enrichment of nitrite
[0069] 12 x 12 cm 2 The Cu-based PVDF membrane was connected to the negative electrode of a DC power supply as a cathode, and two carbon felt anode materials with the same area as the cathode were connected to the positive electrode of the power supply. The positive and negative electrodes were parallel and opposite to each other with a distance of 0.8 cm to construct an electrocatalytic reduction system. The electrocatalytic reduction system was immersed in a nitrate solution at 0.3 mA / cm 2 Under the conditions of constant current density and continuous stirring, nitrate is selectively reduced to nitrite to achieve nitrite enrichment.
[0070] Embodiment 5:
[0071] (1) Preparation of Cu-based PVDF membrane
[0072] After PVDF and polyvinyl pyrrolidone porogen were dried at 88°C for 42 h, 14 g PVDF and 6.8 g polyvinyl pyrrolidone porogen were weighed and added to 79.2 g N, N-dimethylacetamide, and stirred at 87°C for 15 h to prepare a uniform casting solution; after the casting solution was allowed to stand for degassing for 33 h, the casting solution was evenly coated on a Cu / Ni alloy mesh with a thickness of 180 μm and a pore size of 250 μm fixed on a dry glass plate using a scraper, and the coating layer thickness was 380 μm; the Cu / Ni alloy mesh coated with the casting solution was allowed to stand in the air for 9 s and then placed in a deionized water coagulation bath, and after it fell off naturally, it was immersed in deionized water for 66 h, and dried in an oven at 37°C for 42 h to obtain a Cu-based PVDF membrane.
[0073] (2) Electrochemical enrichment of nitrite
[0074] 20 × 20 cm 2 The Cu-based PVDF membrane was connected to the negative electrode of a DC power supply as a cathode, and two carbon fiber cloth anode materials with the same area as the cathode were connected to the positive electrode of the power supply. The positive and negative electrodes were parallel and opposite to each other and kept 1.3 cm apart to construct an electrocatalytic reduction system. The electrocatalytic reduction system was immersed in a nitrate solution at 0.1 mA / cm 2 Under the conditions of constant current density and continuous stirring, nitrate is selectively reduced to nitrite to achieve nitrite enrichment.
[0075] The electrocatalytic reduction system with a Cu-based PVDF membrane as the cathode constructed in Examples 2-4 was loaded into an anaerobic ammonium oxidation membrane bioreactor. Compared with the anaerobic ammonium oxidation membrane bioreactor not loaded with the electrocatalytic reduction system, the experiment showed that the concentrations of nitrate and ammonium salt in the water were significantly reduced. It can be seen that the electrochemical enrichment method of nitrite provided by the present invention can efficiently reduce the nitrate associated with anaerobic ammonium oxidation to nitrite during the long-term operation of the anaerobic ammonium oxidation process, so that nitrite can participate in the anaerobic ammonium oxidation reaction again and further consume ammonium salt, which has a significant effect on improving the denitrification efficiency of the anaerobic ammonium oxidation process.
[0076] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for electrochemical enrichment of nitrite, characterized in that: The method is to selectively reduce nitrate to nitrite by electrocatalytic reaction, thereby achieving nitrite enrichment, and the reduction reaction occurs on the surface of the Cu-based PVDF membrane.
2. The electrochemical enrichment method of nitrite according to claim 1, characterized in that: The following steps are involved: 1) The Cu-based PVDF membrane is used as the cathode and connected to the negative electrode of the DC power supply, and the two anode materials are connected to the positive electrode of the power supply. The cathode and the two anodes are parallel and opposite to each other and maintain a certain distance to construct an electrocatalytic reduction system; 2) The electrocatalytic reduction system is immersed in a nitrate solution, and the nitrate is selectively reduced to nitrite under conditions of constant current density and continuous stirring to achieve nitrite enrichment.
3. The electrochemical enrichment method of nitrite according to claim 2, characterized in that: The distance between the cathode and the anode is 0.5-1.5 cm.
4. The electrochemical enrichment method of nitrite according to claim 2, characterized in that: The constant current density is 0.1-0.3 mA / cm 2 .
5. The electrochemical enrichment method of nitrite according to claim 2, characterized in that: The anode material has the same area as the cathode material.
6. The electrochemical enrichment method of nitrite according to claim 2, characterized in that: The anode material includes one or more of carbon, titanium, platinum, lead, nickel, iridium, ruthenium, stainless steel and boron-doped diamond, and the anode material is in the form of sheet, plate, mesh, cloth or foam.
7. The electrochemical enrichment method of nitrite according to claim 1, characterized in that: The preparation of the Cu-based PVDF membrane comprises the following steps: 1) mixing raw materials including polyvinylidene fluoride, a porogen and an organic solvent to obtain a film casting solution, and coating the film casting solution onto a Cu-based metal mesh; 2) placing the Cu-based metal mesh coated with the plating solution in a coagulation bath to coagulate into a film, and after the film falls off, washing the film in deionized water, and drying to obtain the Cu-based PVDF film.
8. The electrochemical enrichment method of nitrite according to claim 7, characterized in that: The raw materials for preparing the Cu-based PVDF membrane include the following components in parts by weight: 79-83 parts of an organic solvent, 9-15 parts of polyvinylidene fluoride, and 6-8 parts of a porogen.
9. The electrochemical enrichment method of nitrite according to claim 8, characterized in that: The Cu-based metal mesh has a thickness of 100-200 μm and a pore size of 100-300 μm. The material of the Cu-based metal mesh is pure copper, copper oxide, or an alloy of copper or copper oxide and other metals or non-metals.
10. Application of the electrochemical enrichment method of nitrite according to any one of claims 1 to 9 in denitrification by anaerobic ammonium oxidation process.
Citation Information
Patent Citations
High-purity beta-phase PVDF (Polyvinylidene Fluoride) membrane, preparation method and application thereof in preparing piezoelectric diaphragm
CN106925140A
Electrochemical short-cut denitrification nitrogen removal method
CN117185431A
Preparation method and application of composite conductive film capable of being repeatedly torn and recast
CN117531382A
Preparation method and application of three-dimensional structured electric cathode based on cuprous oxide
US20240410066A1
Nanostructured membranes and uses thereof
WO2012153050A1